Butcher's Crossing - Williams, John, 1922-1994 (New York Review Books classics., 2007)
In the 1870s, Will Andrews, fired up by Emerson to seek "an original relation to nature," drops out of Harvard and heads west. He washes up in Butcher's Crossing, a small Kansas town full of restless men looking for ways to make money and ways to waste it. One of these men regales Will with tales of the immense buffalo herds hidden away in the Colorado Rockies and convinces him to join an expedition to track them down. At the end of a grueling journey, the men reach a place of paradisal richness, where they abandon themselves to an orgy of slaughter. So caught up in killing buffalo that they lose all sense of time, the men are overtaken by winter and snowed in. In the spring, half-insane with cabin fever, cold, and hunger, they stagger back to Butcher's Crossing to find a world as irremediably changed as they have been.